Determination and Pharmacokinetic Comparisons of Atractylodin after Oral Administration of Crude and Processed Atractylodis rhizoma - Xiao-Wen, Chang (Pharmacogn Mag, 2016)
BACKGROUND: In traditional Chinese medicine, Atractylodis rhizoma is the dried rhizome of Atractylodes lancea (Thunb.) DC. or Atractylodes chinensis (DC.) Koidz. After being processed, the dryness of A. rhizoma decreased, and the function of tonifying spleen increased. Therefore, the processed A. rhizoma is the best choice of clinical application. As the main active components, polyethylene alkynes exhibits various desirable pharmacological effects including anti-inflammatory, anti-bacterial and anti-arrhythmia activity. However, there is no report on the pharmacokinetic comparisons of atractylodin, one of polyethylene alkynes, in bio-samples after oral administration of crude and processed A. rhizoma until now. The in vivo study of active components of A. rhizoma would be necessary and helpful for clinical application and clarification of processing principle. OBJECTIVE: To compare the pharmacokinetic parameters of atractylodin after oral administration of crude and processed A. rhizoma, and clarify the processing principle of A. rhizoma. MATERIALS AND METHODS: Plasma concentrations of atractylodin in rats were determined by reversed-phase high-performance liquid chromatogram and the main pharmacokinetic parameters were estimated with Drug and Statistics 2.0 Software Package (Chinese Pharmacological Society, Shanghai, China). RESULTS: The AUC(0−t), AUC(0→∞), T(max), and C(max) of processed A. rhizoma were increased significantly (P < 0.05) compared with that in crude A. rhizoma after using Student's t-test. CONCLUSIONS: Processing A. rhizoma with wheat bran by stir-frying can promote and accelerate the absorption of atractylodin. SUMMARY: In this paper, a RP-HPLC method with UV detection for quantification of atractylodin (a main active component in Atractylodis Rhizoma) in rat plasma has been developed and applied to a preliminary pharmacokinetic study of atractylodin after oral administration of crude and processed Atractylodis Rhizoma respectively. The result indicates that processing Atractylodis Rhizoma with wheat-bran can promote and accelerate the absorption of atractylodin.